2015
DOI: 10.5424/sjar/2015133-6880
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Comparison of the efficacy of Apiguard (thymol) and Apivar (amitraz) in the control of Varroa destructor (Acari: Varroidae)

Abstract: The present study compared the efficacy of Apivar (a.i. amitraz) and Apiguard (a.i. thymol) in controlling the mite Varroa destructor during spring 2010 and autumn 2011, in the Balearic Islands (Spain). Number of fallen mites (NFM) was counted weekly and the efficacy of treatments was evaluated by using the percentage of reduction of the average daily fallen mites (%R). During spring assay, the average NFM was highly reduced in Apiguard (89.8%) compared to Apivar (64.3%) group, with significant differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Our finding that in this period organic treatments were more effective than synthetic treatments in reducing Varroa abundance is consistent with another study conducted in Balearic islands (Leza et al, 2015) that obtained a higher efficacy for Apiguard (organic treatment) compared to Apivar (synthetic treatment), both in spring (April to May) and in late autumn (November to December). The most significant impact of treatment was found in the second period of the year, the season in which population sizes of Varroa tend to be lower.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding that in this period organic treatments were more effective than synthetic treatments in reducing Varroa abundance is consistent with another study conducted in Balearic islands (Leza et al, 2015) that obtained a higher efficacy for Apiguard (organic treatment) compared to Apivar (synthetic treatment), both in spring (April to May) and in late autumn (November to December). The most significant impact of treatment was found in the second period of the year, the season in which population sizes of Varroa tend to be lower.…”
Section: Discussionsupporting
confidence: 92%
“…The most significant impact of treatment was found in the second period of the year, the season in which population sizes of Varroa tend to be lower. Our finding that in this period organic treatments were more effective than synthetic treatments in reducing Varroa abundance is consistent with another study conducted in Balearic islands (Leza et al, 2015) that obtained a higher efficacy for Apiguard (organic treatment) compared to Apivar (synthetic treatment), both in spring (April to May) and in late autumn (November to December). Moreover, Loucif-ayad et al (2010) found similar results in a comparative field study of treatments carried out in Algeria, Western Mediterranean, during autumn.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[16][17][18] We detected a drop in the efficacy of coumaphos liquid in the second autumn, probably due to the lower external temperatures or internal (in-hive) conditions like colony population. A similar observation has also been reported by Semkiw et al 17 and Leza et al 19 with the studies of amitraz plastic strip. Although the results of the assessments of amitraz strips in our experiment are high/not variable, some researchers have gained variable results as 83.8% on average (78.8 -87.3%) in Italy and maximum 60.1% efficacy in Portugal.…”
Section: Discussionsupporting
confidence: 88%